A case of mixed mechanism glaucoma: diagnostic and management challenges - Iskandar, Ferdy; Oktariana, Virna Dwi; Aziza, Yulia (Faculty of Medicine Universitas Indonesia, 2025)
Mixed mechanism glaucoma occurs when secondary causes contribute to glaucoma in an eye with preexisting primary open-angle glaucoma (POAG) or primary angle-closure glaucoma. This study highlights its diagnostic and management challenges. A 63-year-old female presented with blurry vision and right eye pain for 2 months. She had undergone cataract surgery in the right eye 6 months earlier and developed elevated intraocular pressure (IOP) afterward. Her visual acuity in the right eye was hand movements, and IOP was 34 mmHg despite medications. Examination revealed signs of uveitis, leading to a diagnosis of secondary glaucoma. A glaucoma drainage device (GDD) was implanted, successfully controlling IOP. Follow-up revealed POAG signs in the left eye, prompting a revised diagnosis of mixed mechanism glaucoma in the right eye. GDD implantation was effective, but continued monitoring remained essential to maintain the target IOP.